Analysis of Micro, Small, and Medium Enterprises (MSMEs) Governance as Supporters of the Gunung Kelud Tourism Area (A Case Study of Kelud Honey Pineapple Traders, Kediri Regency) - Hermawan, Romy (Jurnal Ilmiah Administrasi Publik, 2024)
Sugihwaras Village is a village located in Ngancar Subdistrict, Kediri Regency. A well-known agricultural commodity is pineapple with a typical mainstay product, namely "Kelud honey pineapple". In practice, Kelud honey pineapple traders are part of Micro, Small and Medium Enterprises (MSMEs) and as an aspect of Tourism Amenities to support tourism activities in the Mount Kelud Tourism Area. However, the government's objectives are still not in line with the management conditions of Kelud honey pineapple traders' MSMEs. Therefore, this research will describe how Kelud honey pineapple traders are managed as supporters of the Mount Kelud Tourism Area. This research uses a qualitative method with an exploratory descriptive approach. Data collection techniques use interviews, observation and documentation. Data analysis consists of data collection, data condensation, data presentation, and drawing conclusions. The results of the research show that (1) The management of Kelud honey pineapple traders is considered to be quite good in terms of potential, personal, operational, relationship and interaction management, (2) The obstacles encountered by Kelud honey pineapple traders are related to the provision of facilities, high purchasing prices and sales decreasing. (3) Efforts made by the government include organizing festivals and community training, but there is a need for capital assistance for traders.